Electrodegradation of Resorcinol on Pure and Catalyst-Modified Ni Foam Anodes, Studied under Alkaline and Neutral pH Conditions - Tomasz Mikolajczyk; Boguslaw Pierozynski; Lech Smoczynski; Wieslaw Wiczkowski (Molecules, 2018)
This work reports on the kinetics of electrochemical degradation of the resorcinol molecule, examined on nickel foam-based electrodes in contact with 0.1 M NaOH and 0.5 M Na2SO4 supporting electrolytes. The electrooxidation of resorcinol was examined on as-received, as well as on Pd-modified, nickel foam catalyst materials, produced via spontaneous deposition of trace amounts of palladium element. Electrochemical (cyclic voltammetry and a.c. impedance) experiments were carried out by means of a three-compartment, pyrex glass electrochemical cell, whereas continuous resorcinol electrooxidation tests were conducted galvanostatically (or potentistatically) with a laboratory-size, single-cell electrolyzer unit. In addition, quantitative determination of resorcinol and its possible electrodegradation products was performed by means of instrumental HPLC: High-Performance Liquid Chromatography/MS: Mass Spectrometry methodology. Also, SEM (Scanning Electron Microscopy) and EDX (Energy Dispersive X-ray spectroscopy) techniques were employed for Ni foam (Pd-modified Ni foam) surface characterizations.